Characterization and Prevention of the Adsorption of Surfactant Protein D to Polypropylene - Bratcher, Preston E. (Public Library of Science, 2013)
Surfactant Protein D (SP-D) is a multifunctional protein present in the lung and in respiratory secretions. In the process of developing new experimental approaches to examine SP-D function, we observed that SP-D adsorbs to polypropylene tubes to a great extent, thereby depleting SP-D from the solution. Although it is well known that proteins adsorb nonspecifically to plastic, this effect is usually diminished by treatments to make the plastic “low-retention” or “low-binding”. However, these treatments actually increased the binding of SP-D to the plastic. In addition, this adsorption affected the results of several assays, including proteolytic cleavage assays. In order to block SP-D from adsorbing to polypropylene and the effects caused by this adsorption, we coated the tubes with bovine serum albumin (BSA), as is commonly performed for ELISAs. This coating greatly diminished the amount of SP-D sticking to the plastic, providing an inexpensive and effective method for preventing adsorption and the artifacts resulting from this adsorption.